Using alumina and zirconia ceramic composite in dogs: A biocompatibility study - Korakot Nganvongpanit (2018)
This research was to study the biocompatibility of in-house ceramic materials; consisted of different ratios of magnesium-doped alumina (MDA) and yttria-stabilized zirconia (YSZ). Materials 1-3 (M1-3) were 40, 50 and 60% MDA, respectively. Six male dogs were used for subcutaneous implants in the right hind limb for a 12-week period. Blood was collected from dogs weekly to evaluate health. Tissue surrounding material was then collected for histological evaluation and real-time PCR. Five transcripts, including TNF-α, IL-6, IL-13, IFN-g and MMP-9, were quantified using real-time PCR. The hardness of all materials was tested prior to and after implantation. The results found that all of the biopsy specimens showed neither foreign body reaction no r granulation tissue formation. Compared to the control, expression of MMP-9 in M1 was found to be significantly down-regulated (P < 0.05); expression of TNF-α, IL-13 and MMP-9 in M2 was found to be significantly different (P < 0.05); and in M3, IL-13 was found to be significantly up-regulated (P < 0.05). Hardness in M1 was significantly decreased (P < 0.05) after 12 weeks of implantation. In conclusion, M3, which consisted of 60% MDA, is a candidate material for use as a bone substitute in dogs.